ANALISIS STRATEGI MARKETING DALAMMENINGKATKAN PENJUALAN PADA UMKM DI ERACOVID-19(STUDI KASUS KOPI KATAKITA DI BEKASI) - Muhammad Hazza Ghazali (2022)
This study aims to identify and analyze MSME marketing strategies in increasing sales in the era of the covid-19 pandemic at Kopi KataKita MSMEs in Bekasi. This research method uses descriptive qualitative method with 6 informants. where the researcher is the main instrument of the data collection technique carried out by trigulation (combined), the data analysis is inductive/qualitative, and the results of qualitative research emphasize meaning rather than generalization. The research was conducted by interviewing then observation and documentation and combining it with the 4P marketing mix theory. The results showed that the use of the marketing mix on Kopi KataKita in increasing sales got positive results where the product, price, promotion, and distribution strategies were deemed appropriate or attracted the interest of customers